Study of the Hadith "The Division of the Ummah" and Its Social Impacts - Haqyar, Abdullah (Journal of Social Sciences - Kabul University, 2023)
The Hadith "The Division of the Ummah" has historically been a source of division and conflict among members of the same Ummah. This ongoing discord necessitates scholarly research and investigation to frame the Hadith as a unifying rather than divisive study, interpreted in light of Quranic verses, other prophetic Hadiths, and the overarching objectives of Sharia. This study aims to provide a contemporary analysis of sects and Islamic groups that seek unity and reconciliation, identifying commonalities and peaceful approaches to achieving harmony. The ultimate goal is to foster unity and integration among those who share the same faith, belong to the same Ummah, and face the same Qibla. Despite significant debates concerning the authenticity of the Hadith "The Division of the Ummah," it has often been used as a justification for sectarian division. Each sect attempts to interpret the Hadith to assert the correctness of its doctrine, using it to claim the status of the "Saved Sect." This article critically examines the Hadith's impact on sectarian discourse and its implications for Muslim unity.